PENGARUH KONSENTRASI MADU TRIGONA TERHADAP MUTU MIKROBIOLOGI, KIMIA DAN SENSORIS YOGHURT SARI UBI JALAR UNGU (Ipomoea batatas L.) - Qibtiyah, Riyadhotul; Handayani, Baiq Rien; Ariyana, Mutia Devi (Jurnal Teknologi Hasil Pertanian, 2022)
The objective of this study was to determine the effect of various concentrations of trigona honey on microbial, chemical and sensory quality of purple sweet potato juice yoghurt. The method used in this research was an experimental method with a single factor Completely Randomized Design (CRD), namely concentration of trigona honey 0%; 2.5%; 5%; 7.5%; 10%, and 12.5%. The parameters observed were the total lactic acid bacterial (LAB), total lactic acid, pH, antioxidant activity, viscosity, color, and sensory (aroma, taste, appearance and consistency). Observational data were analyzed by analysis of variance with a significance level of 5% using the Co-stat software. The real difference data was further analyzed using the Honestly Significant Difference (HSD) test for microbial, chemical, and sensory parameters. The result showed that the concentration of trigona honey had a significantly different effect on the total lactic acid bacterial (LAB), total lactic acid, pH, antioxidant activity, viscosity, and sensory properties of taste (hedonic), appearance (hedonic and scoring) and consistency (hedonic and scoring). The use of 5% trigona honey produced purple sweet potato juice yoghurt with the best quality the following characteristics: the total lactic acid bacterial (LAB) 9,89 ± 0,39 log CFU/mL, total lactic acid 1,28 ± 0,016 %, pH 3,48 ± 0,016, antioxidant activity 27,45 ± 1,45 %, viscosity 172 ± 0 cP, color 52,82 ± 2,58 and other acceptable sensory qualities.